Comparison of Histological Characteristics of Dried and Fresh Amnion Membranes and Dura Mater in Non-Human Primate (Macaca fascicularis) - Indah, Astrina Rosaria; Bolly, Hendrikus Masang B.; Faried, Ahmad; Arifin, Muhammad Zafrullah; Achadiyani, Achadiyani; Wirakusumah, Firman Fuad (Majalah Kedokteran Bandung, 2019)
This study aimed to characterize the histological properties of dry-lyophilized amniotic membrane, fresh amniotic membrane (AM), and duramater membrane in search for a biologically-derived material suitable for meninges surface reconstruction. This descriptive study was conducted at the Unit-3 Laboratory of Animal Test of PT. Bio Farma (Persero), Bandung and Cell Biology Laboratory of the Faculty of Medicine, Universitas Padjadjaran Bandung. This study was conducted from 2018-2019. Fresh Macacafascicularis placenta from healthy donors,classified as specific pathogen-free for TB, SIV, SV40, Polio type 1,2,3, Foamy virus and Herpes B virus, were obtained from selected caesarean sections.The harvested dried and fresh AM and duramater membrane were stained with hematoxylin-eosin and prepared for characterization. Histological examination of dry-lyophilized and fresh AM showed similar results. Histologically, AM is represented by a single layer of metabolically-active cuboidal to columnar epithelium with microvilli firmly attached to a basement membrane and an avascular and relatively sparsely populated stroma. Meninges layers consists of 3 layers: duramater, arachnoid membrane, and piamater. Most of these cells have the same characteristics as fibroblasts, including long organelles and nuclei with various levels of fibril formation. The histological study of amniotic membrane and duramater membrane shows comparable results. The AM is a biologically-derived material suitable for meninges surface reconstruction since its histological structure is somewhat similar to that of the duramater. Its structure is ideal for replacing duramater since it has several characteristics, such as having hygroscopic properties, good biocompatibility, relatively easy to apply, and inexpensive. Key words: Dried and fresh amnion membranes, duramater membranes, non-human primate Karakteristik Histologis Membran Amnion Jenis Kering dan Segar dengan Membran Duramater pada Primata Non-Human Macaca fascicularis Penelitian ini bertujuan mengetahui karakteristik histologis membran amnion kering yang diliofilisasi, membran amnion segar, dan duramater, dalam rangka mencari bahan biologis yang cocok untuk rekonstruksi permukaan meninges. Penelitian deskriptif dilakukan di Laboratorium Hewan Uji PT. Bio Farma dan Laboratorium Biologi Sel FK Universitas Padjadjaran periode 2018-2019. Plasenta Primata non-human Macaca fascicularis segar dari donor sehat, yang bebas dari pathogen spesifik TB, SIV, SV40, Polio tipe 1, 2, 3, virus Foamy dan virus Herpes B, diperoleh dari seksio sesarea. Kemudian, dilakukan pewarnaan dengan hematoxylin-eosin untuk membran amnion kering dan segar, serta membran duramater untuk mengetahui karakterisasi histologisnya. Pemeriksaan histologis membran amnion kering-yang aktif bermetabolisme hingga kolumnar dengan mikrovili; melekat kuat pada membran basal dan stroma yang avaskular dan relatif jarang. Lapisan Meninges terdiri dari 3 lapisan: duramater, arachnoid dan piamater. Sebagian besar sel-sel ini memiliki karakteristik yang sama dengan fibroblas. Studi histologis membran amnion dan membran duramater memiliki struktur yang relatif serupa. Membran amnion adalah material yang secara biologis cocok untuk rekonstruksi permukaan meningen, karena struktur histologinya agak mirip dengan duramater. Oleh karena itu secara struktur, membran amnion ideal untuk menggantikan duramater karena memiliki beberapa karakteristik seperti sifat higroskopis, biokompatibilitas baik, mudah diterapkan, dan murah. Kata kunci: Membran amnion segar dan kering, membran duramater, primate non-human